Tashas : franchising the boutique cafe experience - Krost, Peta; Temlett, Sean ([London] : SAGE, 2016)
At the beginning of 2009, Natasha Sideris, owner and founder of Tashas - a hugely popular gourmet cafe in Atholl Square, Sandton - was on the verge of a massive expansion: to open 25 franchises at upmarket centres across South Africa. This book explains how Tashas approached this daunting expansion programme.
Originally Published in: Krost Maunder, P., & Temlett, S. (2009). Tashas: Franchising the Boutique Cafe Experience. WBS-2009-10. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Coffeehouses -- Management -- Case studies; Franchises (Retail trade) -- Case studies